The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s40695-022-00073-y
|View full text |Cite|
|
Sign up to set email alerts
|

Disparities in Reproductive Aging and Midlife Health between Black and White women: The Study of Women’s Health Across the Nation (SWAN)

Abstract: This paper reviews differences in the experience of the menopause transition and midlife health outcomes between Black and White women who participated in the Study of Women’s Health Across the Nation (SWAN), a 25-year, longitudinal, multi-racial/ethnic cohort study. We identify health disparities, i.e., instances in which Black women’s outcomes are less favorable than those of White women, and consider whether structural racism may underlie these disparities. Although SWAN did not explicitly assess structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 116 publications
(160 reference statements)
0
48
0
Order By: Relevance
“…We included race and ethnicity as a variable because of reported racial and ethnic differences in the experience of menopause. 23 Participants had blood samples obtained at enrollment and after 12 weeks of study intervention. In this analysis, we compared serum measurements of estradiol, estrone, and SHBG concentrations in the estrogen vs placebo treatment groups.…”
Section: Methodsmentioning
confidence: 99%
“…We included race and ethnicity as a variable because of reported racial and ethnic differences in the experience of menopause. 23 Participants had blood samples obtained at enrollment and after 12 weeks of study intervention. In this analysis, we compared serum measurements of estradiol, estrone, and SHBG concentrations in the estrogen vs placebo treatment groups.…”
Section: Methodsmentioning
confidence: 99%
“…10 Discrimination was associated with increased measures of pain in both African American and White women, although African American women reported more discrimination. 10…”
Section: Quality Of Lifementioning
confidence: 96%
“…African American women had a higher prevalence of VMS, and experienced VMS more frequently and for longer durations than their counterparts from other racial/ethnic groups. 10,14 The estimated prevalence of VMS is 80% among African American women compared with 65% among White women. The median duration of VMS is 10.1 years in African American women compared with a median of 6.5 years in White women.…”
Section: Vasomotor Symptomsmentioning
confidence: 99%
“…A 2021 international scoping review found that social factors including systemic discrimination, racism, and sexism together with personal factors such as socioeconomic status and beliefs about menopause shaped the experience of menopause in migrant women 11. In the US, menopause is earlier, and vasomotor symptoms more common and long lasting, in African American than in white American women 12. The reasons for these disparities are not known but structural racism, inequalities, and ongoing life stressors may contribute.…”
Section: No Universal Menopause Experiencementioning
confidence: 99%